Specific Inhibition of SRC Kinase Impairs Malignant Glioma Growth In Vitro and In Vivo - Hanna Stedt; Laura Alasaarela; Haritha Samaranayake; Jere Pikkarainen; Ann-Marie Määttä; Ivana Kholová; Aaron S. Parker; Seppo Ylä-Herttuala (Elsevier, 2012)
Malignant glioma is a severe cancer with a poor prognosis. Local occurrence and rare metastases of malignant glioma make it a suitable target for gene therapy. Several studies have demonstrated the importance of Src kinase in different cancers. However, these studies have focused mainly on Src-deficient mice or pharmacological inhibitors of Src. In this study we have used Src small hairpin RNAs (shRNAs) in a lentiviral backbone to mimic a long-term stable treatment and determined the role of Src in tumor tissues. Efficacy of Src shRNAs was confirmed in vitro demonstrating up to 90% target gene inhibition. In a mouse malignant glioma model, Src shRNA tumors were almost 50-fold smaller in comparison to control tumors and had significantly reduced vascularity. In a syngenic rat intracranial glioma model, Src shRNA-transduced tumors were smaller and these rats had a survival benefit over the control rats. In vivo treatment was enhanced by chemotherapy and histone deacetylase inhibition. Our results emphasise the importance of Src in tumorigenesis and demonstrate that it can be efficiently inhibited in vitro and in vivo in two independent malignant glioma models. In conclusion, Src is a potential target for RNA interference-mediated treatment of malignant glioma.